Establishment of epithelial and fibroblast cell cultures and cell lines from primary renal cancer nephrectomies - Yap, Ning Yi; Ong, Teng Aik; Morais, Christudas; Pailoor, Jayalakshmi; Gobe, Glenda C.; Rajandram, Retnagowri (Wiley, 2019)
Renal cell carcinoma (RCC) is one of the most lethal urogenital cancers and effective treatment of metastatic RCC remains an elusive target. Cell lines enable the in vitro investigation of molecular and genetic changes leading to renal carcinogenesis and are important for evaluating cellular drug response or toxicity. This study details a fast and easy protocol of establishing epithelial and fibroblast cell cultures or cell lines concurrently from renal cancer nephrectomy tissue. The protocol involves mechanical disaggregation, collagenase digestion and cell sieving for establishing epithelial cells while fibroblast cells were grown from explants. This protocol has been modified from previous published reports with additional antibiotics and washing steps added to eliminate microbial contamination from the surgical source. Cell characterisation was carried out using immunofluorescence and quantitative polymerase chain reaction. Eleven stable epithelial renal tumour cell lines of various subtypes, including rare subtypes, were established with a spontaneous immortalisation rate of 21.6% using this protocol. Eight fibroblast cell cultures grew successfully but did not achieve spontaneous immortalisation. Cells of epithelial origin expressed higher expressions of epithelial markers such as pan-cytokeratin, cytokeratin 8 and E-cadherin whereas fibroblast cells expressed high α-smooth muscle actin. Further mutational analysis is needed to evaluate the genetic or molecular characteristics of the cell lines. © 2019 International Federation for Cell Biology